A modified filter sqp method as a tool for optimal control of nonlinear systems with spatio-temporal dynamics - Rafajłowicz, Ewaryst (1953- ); Styczeń, Krystyn; Rafajłowicz, Wojciech (Zielona Góra: Uniwersytet Zielonogórski)
Our aim is to adapt Fletcher?s filter approach to solve optimal control problems for systems described by nonlinear Partial Differential Equations (PDEs) with state constraints. To this end, we propose a number of modifications of the filter approach, which are well suited for our purposes. Then, we discuss possible ways of cooperation between the filter method and a PDE solver, and one of them is selected and tested.
Keywords: filter approach; nonlinear programming; optimal control; partial differential equations